2021
DOI: 10.3390/pr9081294
|View full text |Cite
|
Sign up to set email alerts
|

A New Symmetrical Thiazolidinedione Derivative: In Silico Design, Synthesis, and In Vivo Evaluation on a Streptozotocin-Induced Rat Model of Diabetes

Abstract: By activating PPAR-γ, thiazolidinediones normalize glucose levels in animal models of type 2 diabetes and in patients with this pathology. The aim of the present study was to analyze 219 new derivatives in silico and select the best for synthesis, to be evaluated for acute oral toxicity in female rats and for control of diabetes-related parameters in a rat model of streptozotocin-induced diabetes. The best compound was chosen based on pharmacokinetic, pharmacodynamic, and toxicological parameters obtained in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…It has been observed that STZ can produce a rat model with severe weight loss [ 32 ], signs, and symptoms [ 13 , 73 , 74 , 75 , 76 , 77 ] similar to those of diabetic patients. The extent of weight loss is proportional to the dosage [ 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been observed that STZ can produce a rat model with severe weight loss [ 32 ], signs, and symptoms [ 13 , 73 , 74 , 75 , 76 , 77 ] similar to those of diabetic patients. The extent of weight loss is proportional to the dosage [ 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same trend was observed for the other treatments (including FC-114 and FC-122), except for glibenclamide treatment. It has been observed that STZ can produce a rat model with severe weight loss [32], signs, and symptoms [13,[73][74][75][76][77] similar to those of diabetic patients. The extent of weight loss is proportional to the dosage [73][74][75][76].…”
Section: In Vivo Administration Of Fc-114 and Fc-122 In A Wistar Rat ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin resistance in peripheral tissues such as adipose tissue, skeletal muscle, and the liver causes an inability to suppress hepatic glucose production, leading to an uptick in liver glucose release. 5 Chronic hyperglycemia occurs when glucose cannot cross the membrane due to decreased insulin secretion by β-pancreatic cells. 6 Pathogenic effects on the insulin signaling pathway lead to a decrease in the activity of phosphatidylinositol-3-kinase (PI3K) and protein kinase B (PKB), altering transmembrane glucose transport.…”
Section: Introductionmentioning
confidence: 99%